Development of a Low-Cost Device for Measuring Ultraviolet Solar Radiation - Serrano, Antonio; Abril-Gago, Jesús; García-Orellana, Carlos J. (Frontiers in Environmental Science, 2022)
Accurate measurements of solar ultraviolet radiation are needed for air quality monitoring, especially to understand the formation and photolysis of tropospheric ozone near the ground. It is interesting to investigate whether this demand could be met using recently developed low-cost UV sensors and new communication technologies. Despite the promising possibilities, their use is still scarce and their potential applications have not yet been thoroughly explored. This study aims to use low-cost sensors to develop devices that accurately measure solar ultraviolet radiation. The devices should be low-cost, small, portable, and have low power consumption and IoT connectivity. For this purpose, three popular low-cost commercial sensors ML8511, UVM30A and VEML6075 are selected and implemented in several prototypes. The sensors are analyzed in terms of their spectral response, leveling, angular response and comparison with reference data. For that aim, experimental measurements are performed at the radiometric station of the Physics Department of the University of Extremadura in Badajoz, Spain. Results indicate that sensors of the same model might have different calibrations. The leveling and the angular response measurements indicate a strong azimuth dependence for the ML8511 and, especially, VEML6075 sensors, while the UVM30A sensor shows a much weaker dependence, probably due to the use of a circular diffuser. The angular response is identified as the main issue of the sensors, notably limiting their accuracy and preventing a widespread use. With the knowledge gained, a final version with LoRa communication and optimized power consumption is developed. The strength of the LoRa connection is measured at different locations on the University Campus using Receiver Signal Strength Indication. It ranges from -27 dB near the gateway to -122 dB at the farthest location on the Campus. The optimization of the power consumption allows 14 days of autonomy if operating only during daylight hours. The study illustrates the suitability of low-cost sensors for UV applications, provided that a good angular response of the sensors is ensured. It contributes to a wider use of these sensors for the measurement of air quality variables by identifying those characteristics that need to be improved by manufacturers to meet the standards.